2021
DOI: 10.1177/10242589211035040
|View full text |Cite
|
Sign up to set email alerts
|

Making algorithms safe for workers: occupational risks associated with work managed by artificial intelligence

Abstract: It is increasingly common for companies to use artificial intelligence mechanisms to manage work. This study examines the health hazards caused by these new forms of technological management. Occupational risks can be reduced if they are taken into account when programming an algorithm. This study confirms the need for algorithms to be correctly programmed, taking account of these occupational risks. In the same way as supervisors have to be trained in risk prevention to be able to perform their work, the algo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
2
2
1

Relationship

0
5

Authors

Journals

citations
Cited by 17 publications
(19 citation statements)
references
References 18 publications
0
18
0
1
Order By: Relevance
“…It is possible to engineer algorithms to account for occupational risks. As argued by Todolo‐Signes, 44 algorithms can and should be programmed to take into account all known occupational health risks. The content and transparency of digital platform algorithms is an issue taken up by the European Commission's proposed directive on improving the working conditions of people working through digital labor platforms.…”
Section: Discussionmentioning
confidence: 99%
“…It is possible to engineer algorithms to account for occupational risks. As argued by Todolo‐Signes, 44 algorithms can and should be programmed to take into account all known occupational health risks. The content and transparency of digital platform algorithms is an issue taken up by the European Commission's proposed directive on improving the working conditions of people working through digital labor platforms.…”
Section: Discussionmentioning
confidence: 99%
“…Both qualitative research from France (Apouey et al, 2020) and China (Lian & Zhou, 2019) found that managerial controls realised through platform technologies, such as digitalised piece rate and pay linked to customer ratings, may be associated with increased work stress among couriers. In contrast, a large number of research from sociology, human resources management, information technology and labour protection have highlighted the potential mental health risk associated with platform technology features such as gamification, algorithmic management and behavioural control (Bérastégui, 2021; Todolí-Signes, 2021; Woodcock, 2020; Woodcock & Johnson, 2018; Zhou, 2020). This factor needs to be investigated by public health research using more robust methods.…”
Section: Discussionmentioning
confidence: 99%
“…96,100 By implementing algorithmic bias detection and mitigation procedures-algorithmic hygiene-and subjecting algorithms to extensive testing before use, consequential decisions negatively affecting workers can be lessened. 96,101,102…”
Section: Algorithmic Bias and Discriminatory Outcomesmentioning
confidence: 99%
“…121 In the case of algorithm-enabled decision systems, the risk control strategy characterized by a human review of algorithmic outputs, called "humans-in-the-loop," is touted as an effective risk management tool. 102,122 However, humans may not be that effective at algorithmic oversight. 71 Many algorithms are inherently opaque and therefore difficult to audit.…”
Section: Risk Managementmentioning
confidence: 99%
See 1 more Smart Citation